Macroartrópodes e suas inter-relações com atributos do solo em agroecossistemas no semiárido potiguar brasileiro - Mendes, Kellyane da Rocha (Universidade Federal Rural do Semi-Árido, 2020)
The current interest in studying soil macroarthropods comes from the need for sustainable use of the environment and its capacity to act as indicators of soil quality, they are influenced by soil attributes and these by agro-ecosystems, studying their interrelationships. subsidies for the proper planning of agricultural activities and conservation of the productive capacity of the soil. The study aimed to evaluate the relationships between soil macroarthropods and physical, structural and chemical attributes in agroecosystems, in agroecosystems. The research was carried out in the Piracicaba community, municipality of Upanema-RN, considering four agroecosystems: native forest / Latosol (reference area), corn and bean consortium area / Cambisolo, pasture area / Argisol and cashew area / Latosol. Deformed and deformed samples were collected, in layers 0.0-0.10, 0.10-0.20 and 0.20-0.30 (m), to carry out the analysis of the physical, chemical and structural attributes of the soil. Macroarthropods were collected by installing provid-type fall traps, installed in the dry and rainy periods, and subsequently identified, accounted for and classified in taxonomic order. The results were interpreted using multivariate analysis techniques as the main tool, to determine the most sensitive attributes in distinguishing environments. The soil attributes showed variability in the uses and classes of soils, being the variables microporosity, field capacity, permanent wilt point, available water, sand, clay, degree of flocculation, Ca2 +, Mg2 +, sum of bases, soil density , total porosity, macroporosity, electrical conductivity and total organic carbon are the most sensitive in distinguishing environments. The retention of water in the soil varied among the studied agroecosystems, with the areas of native forest and intercropping area corn and beans presenting higher water content in the soil than the other areas. The greater supply of total organic carbon favors the structuring of the soil and greater water retention, especially in soils with a sandy texture. For the macroarthropods, the most abundant orders were: Hymenoptera, Coleoptera, Orthoptera, Diptera, Araneae, Hemíptera and Scutigeromorpha, in less expressive values, organisms of the orders Blatodeae, Scorpiones, Lepdoptera larva, Leptdoptera, Odonata, Chodopoda, Phasmatmat, Phasmatmat, Thysanoptera and Ixodida. The abundance and diversity of soil macroarthropods were influenced by climatic seasonality, with greater abundance in the dry period, and greater diversity in the rainy season. The corn and bean consortium area showed the highest rates of Shanon diversity and Pielou equitability, in the rainy season, the cashew area, in the dry season. The macroarthropod communities found in agroecosystems were influenced by the physical, chemical and structural attributes of the soil, and this existing correlation is evidenced with the use of principal component analysis, where the attributes macroporosity, total organic carbon, microporosity, soil density, texture (sand , silt and clay), Ca² +, K + and cation exchange capacity were the most influential.
Keywords: Análise multivariada; Curva de retenção; Macrofauna edáfica; Usos agropecuários; Multivariate Analysis; Retention curve; Edaphic macrofauna; Agricultural uses; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO